ANALISIS KUALITAS PRODUK, PERSEPSI HARGA DAN LOKASI TERHADAP KEPUTUSAN MEMBELI BAKSO MUKIDI - Dewi Gustiawati Dewi Gustiawati; Salman Paludi (Politeknik Bisnis Indonesia, 2023)
The purpose of this research is to analyze and find out the impact of product quality, perceived price and location on purchasing decisions for Bakso Mukidi in Pulogebang, East Jakarta. The survey, which was conducted between January and February 2023, had a total of 100 respondents. Quantitative method used in this research. After testing the validity and reliability of the results obtained during field data collection. Methods of data analysis using multiple linear regression analysis, correlation coefficient analysis and determination with the help of IBM SPSS 20 software. This study shows that product quality positively influences purchasing decisions, while price does not affect purchasing decisions, and location positively influences purchasing decisions.